Cross-taxa generalities in the relationship between population abundance and ambient temperatures. Issue 1863 (20th September 2017) - Bowler, Diana E.; Haase, Peter; Hof, Christian; Kröncke, Ingrid; Baert, Léon; Dekoninck, Wouter; Domisch, Sami; Hendrickx, Frederik; Hickler, Thomas; Neumann, Hermann; O'Hara, Robert B.; Sell, Anne F.; et al.
Abstract : Identifying patterns in the effects of temperature on species' population abundances could help develop a general framework for predicting the consequences of climate change across different communities and realms. We used long-term population time series data from terrestrial, freshwater, and marine species communities within central Europe to compare the effects of temperature on abundance across a broad range of taxonomic groups. We asked whether there was an average relationship between temperatures in different seasons and annual abundances of species in a community, and whether species attributes (temperature range of distribution, range size, habitat breadth, dispersal ability, body size, and lifespan) explained interspecific variation in the relationship between temperature and abundance. We found that, on average, warmer winter temperatures were associated with greater abundances in terrestrial communities (ground beetles, spiders, and birds) but not always in aquatic communities (freshwater and marine invertebrates and fish). The abundances of species with large geographical ranges, larger body sizes, and longer lifespans tended to be less related to temperature. Our results suggest that climate change may have, in general, positive effects on species' abundances within many terrestrial communities in central Europe while the effects are less predictable in aquatic communities.